2015
DOI: 10.1007/s12264-014-1486-4
|View full text |Cite
|
Sign up to set email alerts
|

New hypothesis and treatment targets of depression: an integrated view of key findings

Abstract: Major depressive disorder (MDD) is a common and devastating psychiatric disorder characterized by persistent low mood, cognitive disorder, and impaired social function. Despite its complex mechanisms, increasing evidence has identified the involvement of neurotrophic factors, inflammatory cytokines, the hypothalamuspituitary-adrenal axis, and glutamate receptors in the pathophysiology of this illness. The present review synthesizes recent research achievements to defi ne the network between different hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 89 publications
2
46
0
Order By: Relevance
“…A new hypothesis regarding depression was presented by Cai et al (2) in their recent review who state that it is important to have an integrated view of the mechanisms underlying depression. Genetic and stress vulnerabilities interplay to initiate a cascade of neurobiological changes that disrupt a dynamic system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new hypothesis regarding depression was presented by Cai et al (2) in their recent review who state that it is important to have an integrated view of the mechanisms underlying depression. Genetic and stress vulnerabilities interplay to initiate a cascade of neurobiological changes that disrupt a dynamic system.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants seemingly exert their therapeutic action through their ability to increase the synaptic content of monoamine neurotransmitters; however, the effects on neurotrophic factors, especially BDNF, also seem to play a role (2,15). A study recently investigated serum proBDNF/BDNF and response to the selective serotonin re-uptake inhibitor fluvoxamine in unmedicated first-episode patients with depression and found that no association between serum levels of proBDNF and BDNF during the treatment period (16).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of action of BDNF in the context of depression in these various brain regions are still unclear. The differential interaction of pre- and post-synaptic BNDF-TRKB pathway with various intra and extracellular signaling systems such as second messenger pathways (including phospholipase Cγ, PI3K and MAPK/ERK pathways), inflammatory cytokines, excitatory glutamatergic neurotransmitters and stress hormones could in part result in the contrasting observations of BDNF levels in the different regions of the brains in relation to depression [35]. …”
Section: Molecular Signalingmentioning
confidence: 99%
“…Major depression disorder (MDD) is one of the most common debilitating mood disorders worldwide and becoming the second leading disease contributing to the years lived with disability by 2013 (Cai, Huang, & Hao, 2015). The prominent and persistent low mood, mental retardation, cognitive impairment, volitional decline and somatic symptoms companied the patients lifelong and impaired their social functions.…”
Section: Introductionmentioning
confidence: 99%